Analisis Bi Rate, Inflasi, dan Nilai Tukar terhadap Tingkat Tabungan pada Bank-Bank Umum Di Indonesia: Sebelum dan Pasca Pandemi Covid-19 - Ginting, Andi Lopa; Hariani, Ermatry (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
There are 3 main impacts in using the BI 7-Day (Reverse) Repo Rate instrument as the new policy interest rate, one of which is increasing the effectiveness of monetary policy transmission through its influence on movements in money market interest rates and banking interest rates. Interest rates will affect the level of savings in society. How effective was this interest rate during the pre-pandemic and post-Covid-19 pandemic periods in influencing people's savings levels? The movement of the savings rate is interesting to observe because this variable will experience quite elastic movements when there is the influence of other macroeconomic variables such as inflation and exchange rates. This research aims to measure the impact of movements in the BI rate, inflation and exchange rate on public savings at commercial banks in Indonesia in 2018-2021. This research uses mixed methods. Mixed method is a research method that combines qualitative and quantitative approaches. This research uses an Explanatory Sequential design, starting with data collection and analyzing quantitative (numerical) data in stage 1 and continuing with collecting and analyzing qualitative data (text) in stage 2 which is built based on the results or findings in stage 1 (Creswell and Clark, 2018). This design aims to provide a deeper explanation based on the results or findings in quantitative research, where the quantitative research uses the Vector Error Correction Model (VECM). The variables used in this research are BI Rate, Inflation, Exchange Rate and Community Savings in commercial banks. The time period analyzed is from 2017-2020. The results of this research prove that the variables that had a significant influence on people's savings levels in the period before the Covid-19 pandemic were inflation and the exchange rate, while the BI rate had no significant influence. In the post-pandemic period, it is proven that the variables that have a significant influence on people's savings levels are the BI rate and inflation, while the exchange rate variable has no significant influence.